3D porous superoleophilic/hydrophobic grapefruit peel aerogel for efficient removal of emulsified-oil from water. Issue 2 (April 2023) - Imran, Muhammad; Islam, Ashraful; Ismail, Fatima; Zhang, Panyue; Basharat, Majid; Ikram, Muhammad; Uddin, Ahmed; Zeb, Shah; Hassan, Qadeer-Ul; Gao, Yongxiang
Abstract: Aerogel with ultra-lightweight, special wettability and porous structure played a potential role in the separation of oil layer/water mixture. In this research cost-effective mesoporous three-dimensional (3D) aerogel was designed and fabricated through a simple and green hydrothermal, synthetic method as a sorbent for efficient treatment of emulsified oil. The -prepared grapefruit peel aerogel exhibits mesoporous structures (2–50 nm) with an average pore size/diameter of 10.21 nm, a surface area of 17.31 m 2 /g and pore volume up to 0.0321 cm 3 /g. Excellent hydrophobicity of DMS-MGA aerogel with a water contact angle of 143.1° depicting great potential of this material for effective separation of water-oil emulsion. Furthermore, the prepared aerogel displayed excellent regeneration capability of more than 98% after eight cycles of sorption–regeneration. The carbonization process destroyed graphite crystals, and a new peak confirmed the alteration. PDMS raised crystallinity indices to 86%. Raman spectroscopy also revealed two peaks at 1498 and 1588 cm −1 linked with carbon's D and G bands. The effective grafting of dimethyl siloxane on DMS-MGA surface resulted in two new strong bands in the FT-IR spectra at 1254 cm −1 (C-H in Si-CH3 ) and 796 cm −1 (Si-O). TGA showed that the total carbon output was 28.5%, which is indicative of its good stability at elevated temperatures. DMS-MGA demonstrated near-complete sorption at a neutral pH of 7 of a crude oil-in-water emulsions. After 15 sorption-regeneration cycles, DMS-MGA still had a sorption efficiency of more than 95% despite being in contact with oil, and its anti-compression stability hadn't changed in the slightest. Highlights: Prepared grapefruit peel-modified aerogel (DMS-MGA) with superoleophilic/ hydrophobic properties. Wettability of DMS-MGA was mostly due to its high porosity and (DMS) coating. DMS-MGA was able to separate oil-water emulsions with an efficiency higher than 98%. A green synthesis converts food waste into a novel adsorbent for environmental and oil-water cleanup.